PENGARUH ETHANOL TERHADAP KESEPATAN BUAH SALAK - Supartha Utama, I Made; P. Gunadnya, Ida Bagus; Wrasiati, Luh P. (Agrotekno; Vol. 11, No. 2 Januari 2005, 2012)
Salak (Salaca edulis Reinw.) is one of Indonesia’s indigenous tropical fruits,which has given a priority being developed as one of an export horticulturalcommodity. One of problems which causes in difficulty of marketing of this fruit isthat it contains high concentration of tannin of which gives an astringent taste of thefruit. Therefore, this research has tried to reduce this taste by applying ethanolsolution and vapor to the intact fruits.The result indicated that by applying ethanol both as solution and vapour hassignificantly reduced the concentration of tannin of the salak fruit. Other beneficialeffects of ethanol were to increase the total soluble solid and reduce the acidity of thefleshy part of the fruit. All these effects could bring a new market development forsalak fruit. Further research, however, should be performed to identify the minimumconcentration of ethanol in the fleshy of the fruit to give significant reduction of thetannin and the threshold concentration of ethanol to give a taste of ethanol in thefleshy fruit.
Keywords: Salak, ethanol, ethyl alcohol, astringency, senyawa volatile